Život kao artefakt: Matoševo autorstvo. Povodom knjige Dubravke Oraić Tolić Čitanja Matoša - Protrka Štimec, Marina (Wydawnictwo Nauka i Innowacje, 2014)
Paper deals with a conception of Antun Gustav Matoš authorship, regarding his own definition of his life as a work of art. Performing his authorship in a variety of literary texts, letters and notices, he lived in extremes, being flaneur, dandy and a bohem, world traveler and a nationalist ideologist, what infl uenced reception of his work until recent period. Critical and historiographic, as much as other literary works related to AGM follow this „author-centered” positions regarding his life as a work of art, as much as his literary texts as a refl ection of his life. Latest Croatian „Matosiana” book, Dubravka Oraić Tolić̕Reading Matoš (Čitanja Matoša, 2013), attests some traditional critical assumptions regarding authorship of this canonical writer end expands them in a new context. Different theories of literary canon formation, especially those grounded on feminist or psychoanalytical approach, call in question usual strategies in creation and understanding AGM̕ s authorship, aestheticism and anti-modernism.
Life as a Work of Art: Matoš’ Authorship. Regarding Dubravka Oraić Tolić’ book Čitanja Matoša
Keywords: Antun Gustav Matoš; authorship; critical reception; Croatian literature; Dubravka Oraić Tolić; flâneur; dandy bohem; nation; identity